2019
DOI: 10.2298/vsp161223147v
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of quality of life of patients with chronic obstructive pulmonary disease

Abstract: Background/Aim. Chronic obstructive pulmonary disease (COPD) has a significant impact on quality of life of patients. We investigated which demographic and social characteristics can predict the global quality of life (QoL) of COPD patients. Methods. The patients (n = 288) were divided into three groups according to the stage of disease: Group I = stage 0-at risk; Group II = Stages I and II; Group III = stages III and IV. The patients fulfilled a questionnaire related to the demographic and social characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Consistent with our findings, two previous studies showed that elderly patients with COPD suffer from low HRQoL, especially in the physical dimension [26,27]. In some other studies, old age was one of the predictors of physical activity [12], which was found to be associated with the decreased quality of life in these patients [28,29]. Elderly patients with COPD have less body strength compared to healthy individuals.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Consistent with our findings, two previous studies showed that elderly patients with COPD suffer from low HRQoL, especially in the physical dimension [26,27]. In some other studies, old age was one of the predictors of physical activity [12], which was found to be associated with the decreased quality of life in these patients [28,29]. Elderly patients with COPD have less body strength compared to healthy individuals.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, a prior study found that the experience of frequent coughs and wheezing in the previous 12 months is an important risk factor for the low physical and psychological domain of quality of life among the elderly with respiratory diseases [37]. In addition, it has been revealed that the exacerbation of the disease is associated with the low quality of life of patients with COPD [12]. A prior study has revealed that the most worrying symptom affecting the quality of life was shortness of breath [20].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations